Hypoxia in Leishmania major skin lesions impairs the NO-dependent leishmanicidal activity of macrophages - Mahnke, Alexander; Meier, Robert J.; Schatz, Valentin; Hofmann, Julian; Castiglione, Kirstin; Schleicher, Ulrike; Wolfbeis, Otto S.; Bogdan, Christian; Jantsch, Jonathan (Journal of Investigative Dermatology, 2014)
Cure of infections with Leishmania major is critically dependent on the ability of macrophages to induce the type 2 nitic oxide (NO) synthase (NOS2) that produces high levels of NO in the presence of ample oxygen. Therefore, we analyzed the oxygen levels found in leishmanial skin lesions and their effect on the NOS2-dependent leishmanicidal activity of macrophages (M?). When L. major skin lesions of self-healing C57BL/6 mice reached their maximum size, the infected tissue displayed low oxygen levels (pO2 21 Torr). M? activated under these oxygen tensions failed to produce sufficient amounts of NO to clear L. major. Nos2-deficient and hypoxic wild-type macrophages displayed a similar phenotype. Killing was restored when M? were reoxygenated or exposed to a NO donor. The resolution of the lesion in C57BL/6 mice was paralleled by an increase of lesional pO2. When mice were kept under normobaric hypoxia, this caused a persistent suppression of the lesional pO2 and a concurrent increase of the parasite load. In Nos2-deficient mice, there was no effect of atmospheric hypoxia. Low oxygen levels found at leishmanial skin lesions impaired the NOS2-dependent leishmanicidal activity of M?. Hence, tissue oxygenation represents an underestimated local milieu factor that participates in the persistence of Leishmania.
EVALuna2:7645

Myeloid Cell-Derived HIF-1? Promotes Control of Leishmania major - Schatz, Valentin; Strussmann, Yannic; Mahnke, Alexander; Schley, Gunnar; Waldner, Maximilian; Ritter, Uwe; Wild, Jens; Willam, Carsten; Dehne, Nathalie; Brune, Bernhard; Mcniff, Jennifer M.; Colegio, Oscar R.; et al. (Journal of Immunology, 2016)
Hypoxia-inducible factor-1? (HIF-1?), which accumulates in mammalian host organisms during infection, supports the defense against microbial pathogens. However, whether and to what extent HIF-1? expressed by myeloid cells contributes to the innate immune response against Leishmania major parasites is unknown. We observed that Leishmania-infected humans and L. major-infected C57BL/6 mice exhibited substantial amounts of HIF-1? in acute cutaneous lesions. In vitro, HIF-1? was required for leishmanicidal activity and high-level NO production by IFN-?/LPS-activated macrophages. Mice deficient for HIF-1? in their myeloid cell compartment had a more severe clinical course of infection and increased parasite burden in the skin lesions compared with wild-type controls. These findings were paralleled by reduced expression of type 2 NO synthase by lesional CD11b(+) cells. Together, these data illustrate that HIF-1? is required for optimal innate leishmanicidal immune responses and, thereby, contributes to the cure of cutaneous leishmaniasis.
EVALuna2:2181

Ratiometric luminescence 2D in vivo imaging and monitoring of mouse skin oxygenation - Hofmann, Julian; Meier, Robert J.; Mahnke, Alexander; Schatz, Valentin; Brackmann, Florian; Trollmann, Regina; Bogdan, Christian; Liebsch, Gregor; Wang, Xu Dong; Wolfbeis, Otto S.; Jantsch, Jonathan (Methods and Applications in Fluorescence, 2013)
Tissue oxygenation plays a critical role in the pathogenesis of various diseases, but non-invasive, robust and user-friendly methods for its measurement in vivo still need to be established. Here, we are presenting an in vivo oxygen-detection system that uses ratiometric luminescence imaging (RLI) as a readout scheme to determine the skin oxygen tension of mouse hind footpads via side-by-side comparison with more established techniques including luminescence-lifetime imaging using planar sensor films and the polarographic electrode as the gold standard. We also demonstrate that this technology allows the detection of changes in mouse skin tissue oxygenation induced by subjecting mice to systemic hypoxia. The data demonstrate oxygen imaging based on RLI to be a most useful tool for reliably and easily analyzing and monitoring skin tissue oxygenation in vivo. This technology will advance our understanding of local regulation of skin tissue oxygenation in various disease conditions.
CRIS-Team Scopus Importer:2024-02-26